Virulence, Antimicrobial Resistance Properties and Phylogenetic Background of Non-H7 Enteropathogenic Escherichia coli O157 - Ferdous, Mithila; Kooistra-Smid, Anna M. D.; Zhou, Kai; Rossen, John W. A.; Friedrich, Alexander W. (Frontiers in Microbiology, 2016)
Escherichia coli (E. coli) O157 that do not produce Shiga toxin and do not possess flagellar antigen H7 are of diverse H serotypes. In this study, the antibiotic resistance properties, genotype of a set of virulence associated genes and the phylogenetic background of E. coli O157:non-H7 groups were compared. Whole genome sequencing was performed on fourteen O157:non-H7 isolates collected in the STEC-ID-net study. The genomes were compared with E. coli O157 genomes and a typical Enteropathogenic E. coli (tEPEC) genome downloaded from NCBI. Twenty-six (86%) of the analyzed genomes had the intimin encoding gene eae but of different types mostly correlating with their H types, e.g., H16, H26, H39 and H45 carried intimin type ε, β, κ and α, respectively. They belonged to several E. coli phylogenetic groups, i.e., to phylogenetic group A, B1, B2 and D. Seven (50%) of our collected O157:non-H7 isolates were resistant to two or more antibiotics. Several mobile genetic elements, such as plasmids, insertion elements and pathogenicity islands, carrying a set of virulence and resistance genes were found in the E. coli O157:non-H7 isolates. Core genome phylogenetic analysis showed that O157:non-H7 isolates probably evolved from different phylogenetic lineages and were distantly related to the E. coli O157:H7 lineage. We hypothesize that independent acquisition of mobile genetic elements by isolates of different lineages have contributed to the different molecular features of the O157:non-H7 strains. Although distantly related to the STEC O157, E. coli O157:non-H7 isolates from multiple genetic background could be considered as pathogen of concern for their diverse virulence and antibiotic resistance properties.